A síndrome de Burnout em servidores públicos do Departamento Estadual de Trânsito do Amazonas - Nazareth, Sarah da Silva (Brasil, 2024)
The aim of this research was to investigate the incidence of Burnout Syndrome as a consequence of adverse working conditions, by observing 4 civil servants from a state traffic agency in Amazonas, based in Manaus. A qualitative approach was used as the analytical tool. The data was collected through open-ended interviews and a semi-structured questionnaire based on the Maslach Burnout Inventory (MBI) adapted for qualitative study and then examined using the content analysis technique. The results of the research show the absence of Burnout Syndrome in the civil servants, however, they still have symptoms which, if left untreated, can worsen and trigger professional burnout. Symptoms of depersonalization are almost non-existent, the relationship between co-workers was described as harmonious and healthy, linked to good relationships with users, empathy, the desire to help and the recognition they receive as a result of providing services. Levels of emotional exhaustion were high, due to the long working hours and excessive demands. In relation to professional development, levels are low, due to frustrations with the institution and inefficient management, coupled with low pay, little recognition and a lack of resources for training. These factors contribute significantly to the gradual development of burnout.